Are We Measuring Teachers’ Attitudes towards Computers in Detail?: Adaptation of a Questionnaire into Turkish Culture - Nilgün Günbaş; Özden Demir (International Journal of Assessment Tools in Education)
Teachers’ perceptions of computers play an important role in integrating computers into education. The related literature includes studies developing or adapting a survey instrument in Turkish culture measuring teachers’ attitudes toward computers. These instruments have three to four factors (e.g., computer importance, computer enjoyment, computer confidence) and 18 to 26 items under these factors. The purpose of the present study is to adapt a more detailed and stronger survey questionnaire measuring more dimensions related to teachers’ attitudes. The source instrument was developed by Christensen and Kenzek (2009) and called Teachers’ Attitudes toward Computers (TAC). It has nine factors with 51 items. Before testing the instrument, the interaction (e-mail) factor was taken out because of the cultural differences. The reliability and validity testing of the translated instrument was completed with 273 teachers’ candidates in a Faculty of Education in Turkey. The results showed that the translated instrument (Cronbach’s Alpha: .94) included eight factors and consisted of 42 items under these factors, which were consistent with the original instrument. These factors were: Interest (α: .83), Comfort (α: .90), Accommodation (α: .87), Concern (α: .79), Utility (α: .90), Perception (α: .89), Absorption (α: .84), and Significance (α: .83). Additionally, the confirmatory factor analysis result for the model with eight factors was: RMSEA=0.050, χ2/df=1.69, RMR=0.075, SRMR=0.057, GFI= 0.81, AGFI= 0.78, NFI= 0.94, NNFI=0.97, CFI=0.97, IFI= 0.97. Accordingly, as a reliable, valid and stronger instrument, the adapted survey instrument can be suggested for the use in Turkish academic studies.